2021
DOI: 10.21062/mft.2021.070
|View full text |Cite
|
Sign up to set email alerts
|

Measuring propeller pitch based on photogrammetry and CAD

Abstract: There are a number of methods for measuring propeller pitch, but there could still be problems for many fishing boat builders because of their lack of necessary professional equipment. This paper presents a method of propeller pitch measuring based on photogrammetry and CAD (Computer-Aided Design). This method consists of three stages. The first stage is to take a series of 2D image photographs of the propeller using a smart phone. The second stage consists of processing these 2D images using photogrammetry so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition to the large thematic groups described above, one can find a number of publications in which 3D models of various objects were made using images taken from a phone [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Smartphones were also used in radioactivity detection [ 94 ] or in forensic science [ 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the large thematic groups described above, one can find a number of publications in which 3D models of various objects were made using images taken from a phone [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Smartphones were also used in radioactivity detection [ 94 ] or in forensic science [ 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through many tests, we found that errors in the image processing process can occur if the object to be photographed has a smooth and uniform surface. In order to facilitate the image processing task in Agisoft Mateshape and obtain a highly accurate virtual model, a cylinder can be used [9]. In this study, this cylinder is made of plastic with a blind hole to put on any finger.…”
Section: Fig1 Picture Capturing Arrangementmentioning
confidence: 99%
“…In Agisoft Metashape, there are four main stages for image processing and 3D surface modelling [9]. First, photos are loaded and camera alignment is performed, then a sparse point cloud and a collection of camera positions is constructed.…”
Section: Image Processing and 3d Surface Modellingmentioning
confidence: 99%
“…It is evident that expert 3D scanning systems can produce very good results, but they are still costly and need highly skilled workers to operate. Reconstructing a physical object's 3D model from its 2D images is now possible with photogrammetry [1,11]. Therefore, instead of expensive 3D scanning systems, smartphone cameras and certain techniques can be used to obtain 2D images of an arm, which can then be further processed to create a CAD model of the arm [1].…”
Section: Introductionmentioning
confidence: 99%